Numeracy development training for elementary school students at SD Muhammadiyah 2 Waru Sidoarjo - Nuril Lutvi Azizah; Vevy Liansari; Alfan Indra Kusuma (Community Empowerment, 2023)
Covid-19 pandemic has caused the decline in the numeracy ability of low-grade students at SD Muhammadiyah 2 Waru Sidoarjo. Students’ ability dropped by 50%, which cause teacher unable to continue to a higher numeracy level. The purpose of this program is to develop the numeracy skills of low-grade elementary school children at SD Muhammadiyah 2 Waru Sidoarjo. The method used in the form of training for low-grade students (grade 1, 2, and 3) which begins with a pre-test and ends with a post-test. Training is carried out by providing a stimulus for learning numeracy using modern methods through applications on gadgets and conventional methods and exercises. The result obtained from this training were that low-grade students felt interested and enjoyed learning numeracy with modern media than conventional methods. Training using modern numeracy media can increase students’ abilities and interest in learning numeracy.